Determinants Impacting the Triple Bottom Line Sustainability Performance in SMEs: A Systematic Literature Analysis and Future Research Agenda - Naharuddin, Nur Syahirah; Abdul Rahim, Ramita; Ngah, Rohana (Advances in Social Sciences Research Journal, 2024)
Identifying the factors that influence sustainable performance in Small and Medium Enterprises (SMEs) is crucial. However, few studies have comprehensively examined the Triple Bottom Line (TBL) which are economic, social, and environmental aspects of sustainable performance within a single research framework. A systematic review of articles published from 2019-2023 analysed 45 out of 358 papers from 8 databases. The in-depth reading results reveal three clusters representing the main research topics: green and environmental management issues; social and cultural issues; and the necessary values, skills, and capabilities. The findings suggest that future research could focus on green and environmental management issues which adopting sustainable supply chain management, green innovation, and sustainable manufacturing practices, as well as the attributes and competencies SMEs need for sustainability, including the role of training, leadership, and organisational culture in sustainability initiatives.